Metabolic reprogramming and immunological changes in the microenvironment of esophageal cancer: future directions and prospects - Zhi-Xun Guo; Jia-Li Ma; Jin-Qiu Zhang; Ling-Ling Yan; Ying Zhou; Xin-li Mao; Xin-li Mao; Xin-li Mao; Shao-Wei Li; Shao-Wei Li; Shao-Wei Li; Xian-Bin Zhou; et al. (Frontiers in Immunology)
BackgroundEsophageal cancer (EC) is the seventh-most prevalent cancer worldwide and is a significant contributor to cancer-related mortality. Metabolic reprogramming in tumors frequently coincides with aberrant immune function alterations, and extensive research has demonstrated that perturbations in energy metabolism within the tumor microenvironment influence the occurrence and progression of esophageal cancer. Current treatment modalities for esophageal cancer primarily include encompass chemotherapy and a limited array of targeted therapies, which are hampered by toxicity and drug resistance issues. Immunotherapy, particularly immune checkpoint inhibitors (ICIs) targeting the PD-1/PD-L1 pathway, has exhibited promising results; however, a substantial proportion of patients remain unresponsive. The optimization of these immunotherapies requires further investigation. Mounting evidence underscores the importance of modulating metabolic traits within the tumor microenvironment (TME) to augment anti-tumor immunotherapy.MethodsWe selected relevant studies on the metabolism of the esophageal cancer tumor microenvironment and immune cells based on our searches of MEDLINE and PubMed, focusing on screening experimental articles and reviews related to glucose metabolism, amino acid metabolism, and lipid metabolism, as well their interactions with tumor cells and immune cells, published within the last five years. We analyzed and discussed these studies, while also expressing our own insights and opinions.ResultsA total of 137 articles were included in the review: 21 articles focused on the tumor microenvironment of esophageal cancer, 33 delved into research related to glucose metabolism and tumor immunology, 30 introduced amino acid metabolism and immune responses, and 17 focused on the relationship between lipid metabolism in the tumor microenvironment and both tumor cells and immune cells.ConclusionThis article delves into metabolic reprogramming and immune alterations within the TME of EC, systematically synthesizes the metabolic characteristics of the TME, dissects the interactions between tumor and immune cells, and consolidates and harnesses pertinent immunotherapy targets, with the goal of enhancing anti-tumor immunotherapy for esophageal cancer and thereby offering insights into the development of novel therapeutic strategies.